Graft versus host disease after liver transplantation following radiotherapy for the treatment of hepatocellular carcinoma: A case report and literature review. (May 2022) - Chen, Zijun; Han, Chuangye; Wang, Xiangkun; He, Yongfei; Liang, Tianyi; Mo, Shutian; Li, Xuan; Zhu, Guangzhi; Su, Hao; Ye, Xinping; Lv, Zili; Shang, Liming; et al.
Graft versus host disease after solid organ transplantation is very rare. This article reports a case of graft versus host disease after liver transplantation following targeted therapy and radiotherapy for the treatment of hepatocellular carcinoma. The patient developed a symptomatic skin rash and pancytopenia 13 days after surgery, which was confirmed as graft versus host disease after liver transplantation by histopathology and fluorescence in situ hybridization. Early diagnosis of graft versus host disease after solid organ transplantation is difficult and often delayed due to nonspecific manifestations that overlap with other diseases. Currently, the treatment of graft versus host disease after liver transplantation occurs by either strengthening the immune suppression or weakening the immune suppression; however, there is no unified standard treatment strategy. We found that in addition to age, gender, and human leukocyte antigen type, preoperative radiotherapy is a likely risk factor for graft versus host disease after liver transplantation.